Pengaruh Model Pembelajaran Blended Learning Dan Disiplin Belajar Terhadap Hasil Belajar Siswa Di Masa Pandemi Pada Mata Pelajaran Ekonomi SMA N 16 Padang - Nikhen Falinda; Jimmi Ronal; Nilma Desrirosya (STKIP PGRI Sumatera Barat, 2022)
This research is motivated by the teaching and learning process is still conventional so that it makes it difficult for students to understand Economics lessons because the material is abstract. This study aims to determine the effect of learning outcomes after using the blended learning model and student learning discipline. This type of research is quantitative. The study was conducted at SMA N 16 Padang with a population of 154 and a sample of 76 students consisting of 37 students in the experimental class and 39 students in the control class. The research instrument was conducted through the distribution of questionnaires and tests. The data analysis techniques used are validity test, reliability test, level of difficulty, discriminatory power, normality test, homogeneity test and two-way anova test. The study found that: First, students who were taught using the Blended learning model had significantly higher learning outcomes compared to students who were taught through conventional methods.Second, students with high learning discipline have significantly higher learning outcomes than students with low learning discipline. Third, there is no interaction between the blended learning model and discipline on the learning outcomes of class XI students at SMA N 16 Padang. The results of the two-way anova calculation for testing the third hypothesis are shown in the table above, the sig level value is obtained. = 0.100, this means that the value of sig. is greater than the value of = 0.05 (sig < ) then H0 is accepted. Ha is rejected, so there is no interaction between blended learning models and learning disciplines on student learning outcomes in economics subjects for class XI SMA N 16 Padang. Keywords: Blended Learning, Learning Disciplines, Learning Outcomes